Studi Dampak Penggunaan Insulasi pada Bangunan Rumah Tinggal Terhadap Konsumsi Energi Pendingin Ruangan - Roy Candra P Sigalingging (Journal of Science and Applicative Technology, 2021)
The global warming issue has become a concern for environmentalists activists, including many governments. This concern is due to the increasing attention to reducing the use of fossil energy because fossil energy has significantly exacerbated global warming. To minimize the use of fossil energy, especially the housing sector that is one of the extensive energy users. Building performance's analysis is done by creating changes to the case study's building envelope material. Case study buildings were simulated in energy analysis software. Preliminary analysis shows how the performance of the case study building is still far from the standard of thermal comfort. Air conditioning (AC) usage in the room will give comfort in terms of temperature. But, even though with the AC, the humidity level of the room was still high. Two building models are then created in the software to see the performance of the building by making changes to the building envelope material. With the settings on air-conditioning (AC) and environmental conditions in both models, the results indicate differences in the building performance of the two buildings. The results show that the building with insulation are using less energy and can provide optimal comfort for building users. Comfort is not only in terms of the building's temperature but including building relative humidity. In buildings with insulation, the temperature and humidity of the building are relatively stable throughout the year.